Theory and estimation in models of crime and its social control and their relations to concepts of social output - Carr-Hill, Roy A. (The economics of public services, 1977)
Following a short introduction, consideration is given (section II) to a model, developed by Becker (1968), that attempts to describe the generation of, and optimum punishment for, illegal activity. It is shown that this model has no optimum finite solution for the case where punishment is costless (fines, according to Becker). Possible modifications are then discussed and it is suggested that the notion of retribution is required in order to explain observed penalties.